Islamic Information Literacy In Islamic Religious Education Learning - Era Octafiona (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
SMP Negeri 1 Kota Agung has implemented a culture of literacy as a means to improve students' insights, supported by adequate reading book facilities for grades VII to IX. The implementation of literacy is carried out in the morning with a descriptive qualitative field research approach, which collects main and additional data through observation, interviews and documentation. Data analysis was carried out using data reduction, data presentation, conclusion drawing and verification techniques, and using triangulation of sources, techniques and time to ensure data validity. The results showed that Islamic information literacy planning at SMPN 1 Kota Agung has been well integrated by PAI teachers through the preparation of lesson plans and regular meetings. The implementation of Islamic literacy focuses on religious habituation activities carried out every day and once a week, as well as through intracurricular activities such as reciting the Qur'an before learning. Evaluation of Islamic information literacy activities is considered very effective in shaping students' positive behavior.